ChemInform Abstract: Boc‐Protected 1‐(3‐Oxocycloalkyl)ureas via a One‐Step Curtius Rearrangement: Mechanism and Scope. Issue 26 (1st July 2014) - Sun, Xianyu; Rai, Rachita; Deschamps, Jeffrey R.; MacKerell, Alexander D. Jr.; Faden, Alan I.; Xue, Fengtian
Abstract Treatment of carboxylic acids (I) with Et3N, DPPA, and tBuOH provides the title ureas as major products via Curtius rearrangement followed by an unexpected nucleophilic addition of the resulting tert‐butyl carbamate to an in situ generated isocyanate intermediate.